Mathematical modelling driven by two industrial applications: A moving‐boundary approach - Narimanyan, A.; Muntean, A. (Mathematical Modelling and Analysis, 2006)
This note emphasizes the application of the moving‐boundary methodology in the modelling of two processes of particular industrial relevance. The first model explains the application of the Stefan and Signorini type boundary conditions in the modelling of the thermal cutting of metals by a plasma beam, while the second model shows how interface kinetic conditions, employed within the framework of a two‐phase Stefan‐like model, can describe the dynamics of an aggressive reaction front in concrete‐based materials. Our formulations provide a conceptually new approach towards the understanding of the involved physical processes. The connection between the two models is discussed as well. It relies on the presence of non‐equilibrium conditions driving the moving interface. First Published Online: 14 Oct 2010